Sabhuku vharazipi’ (2012) and the cultural imperatives of community theatre - Rwafa, Urther (UNISA Press, 2016)
The aim of this paper is to explore the dramatic and thematic possibilities of a theatrical piece, Sabhuku Vharazipi, written and directed by Wellington Chindara of Ziya Cultural Theatre Club. Rendered in the Shona language, this theatrical piece is a social commentary that caricatures the corruptible tendencies of the local leadership in Zimbabwe. Through its dramatic text, Sabhuku Vharazipi comments on lust, greed, corruption, bribery, nepotism, gender struggles and the slow pace of community development in Zimbabwe. The theme of corruption that is very visible and prominent in this theatrical piece mirrors the depth of moral “rottenness” that is threatening to destroy Zimbabweans as a nation. As a meta-narrative, Sabhuku Vharazipi is saying that unless something positive is done to “nip corruption in the bud”, Zimbabwe is unlikely to relive those golden years (early 1980s) when people used to be rewarded through merit or hardworking, not through corruption and laziness.